Morphometric relationships and size at sexual maturity of the deep-sea Caribbean lobster Metanephrops binghami (Decapoda: Nephropidae) in the Colombian Caribbean - Cusba, José; Universidad del Magdalena, Grupo de Investigación Ciencia y Tecnología Pesquera Tropical (CITEPT). Carrera 32 No. 22-08 Avenida del Ferrocarril, Santa Marta. (2017)
This paper describes the morphometric relationships and size at sexual maturity of deep-sea Caribbean lobster. Data were obtained in the Colombian Caribbean in four trawling surveys in November and December 2009 between 200 and 550 m depth. 709 individuals with sizes between 53.65 and 191.00 mm (TL) (mean 121.17 ± 27.13 mm) were measured. M. binghami had a positive allometric growth. Lobsters of the family Nephropidae have a worldwide distribution and economic importance. High levels of biomass of Metanephrops binghami have been reported in the Colombian Caribbean and this species could become a potential new resource for the Western Atlantic fishery. However, prior to the development of a new fishery, more biological research is needed to understand the life cycle of this species. Aspects such as growth, spawning, recruitment, mortality, nursery areas and associated biodiversity should be carefully studied.